I am considering the problem of finding all functions $f:(0,\infty)\to(0,\infty)$ satisfying the functional equation:

$$f\big(xf(y)+f(x)\big) = 2f(x)+xy\text.$$

I have been able to prove the following three results/properties:

  1. $f$ is not surjective.
  2. $f$ does not have any fixed points.
  3. $f(x)=x+1$ is a solution.

My intuition tells me that $x\mapsto x+1$ is the only solution, but I have not been successful in proving or disproving this claim.

Any ideas on how I can make further progress is appreciated.

  • $\begingroup$ You could set $f(x):=g(x)+x+1$. Then - if I did not make any mistakes - the equation will change into: $g\left(xg\left(y\right)+g\left(x\right)+2x+xy+1\right)+xg\left(y\right)=g\left(x\right)$ and the question is now: is $g(x)=0$ the only solution? I really don't know whether that will help, though. $\endgroup$ – drhab Sep 3 '18 at 8:04
  • $\begingroup$ Thanks, the idea is great. But this new equation for g(x) seems to be almost as complicated as the original. $\endgroup$ – Wuberdall Sep 3 '18 at 9:34
  • $\begingroup$ Injectivity can be easily established also. $\endgroup$ – Sil Apr 7 '19 at 10:19
  • 1
    $\begingroup$ In this form it has a solution for example this: artofproblemsolving.com/community/c6h611705p3637387. $\endgroup$ – Sil Jul 18 '20 at 15:32
  • 1
    $\begingroup$ @MohsenShahriari I prefer to add some additional info / thoughts, but I haven't checked this one too thoroughly. Anyway added as a wiki post with the reference at least, anyone can also improve it as necessary. $\endgroup$ – Sil Oct 12 '20 at 10:57

As suggested in comments, here is a solution by user pco in https://artofproblemsolving.com/community/c6h611705p3637387:

Let $P(x,y)$ be the assertion $f\big(xf(y)+f(x)\big)=2f(x)+xy$. Let $a=f(1)$.

$P(1,x) \implies f\big(f(x)+a\big)=x+2a$ and so $(2a, +\infty) \subseteq f(\mathbb{R})$

$P\big(1,f(x)+a\big) \implies f(x+3a)=f(x)+3a$ and so $f(x+3ka)=f(x)+3ka$ $\forall x >0, \forall k \in \mathbb{Z}_{\ge 0}$.

Let $x,y>0$ and $n \in \mathbb{N}$ such that $y+3na>2ax+f(x)$. Then there is $t>0$ such that $y+3na=xf(t)+f(x)$. Comparing $P(x,t)$ with $P(x,t+3a)$, we get $f(y+3na+3ax)=f(y+3na)+3ax$ and so $f(y+3ax)=f(y)+3ax$. So $f(x+y)=x+f(y)$ $\forall x,y >0$ and so $f(x)=x+c$ $\forall x$ and for some $c \in \mathbb{R}$.

Plugging this back in original equation, we get $c=1$ and so the unique solution is $f(x)=x+1$ $\forall x$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.